Glycoprotein G-Based Vaccines for Nipah Virus: Epidemiology, Molecular Insights, Benefits, and Limitations - Mariia, Murzaeva; Qasim, Imad Ghanem; Ismael, Sajida Hussein; Jamal, Zahaa Aldeen; Sharad, Abdalfattah; Najmuldeen, Hastyar Hama; Aryntayeva, Nurila (Trends in Immunotherapy, 2025)
Nipah virus (NiV) is a highly virulent zoonotic pathogen associated with significant mortality rates and limited treatment options, posing a significant public health threat. This review explores the epidemiology, molecular structure, and vaccine development efforts targeting glycoprotein G, a critical component of the virus’s entry mechanism. Advances in structural biology and immunogenetics have highlighted the potential of glycoprotein G-based vaccines in preventing NiV infections. Despite promising preclinical results, challenges such as immune evasion, safety concerns, and limited clinical trials persist. Additionally, we examine the benefits of glycoprotein G-based vaccines in enhancing immune responses and preventing viral entry, as well as the limitations posed by genetic diversity and cross-reactivity. This review highlights the critical need for ongoing research to overcome existing challenges and guide future vaccine development efforts against NiV. It further underscores the necessity of innovative approaches in vaccine design to reduce the global burden of NiV infections. Glycoprotein G-based vaccines represent a promising avenue for combating NiV infections. Advances in structural biology, immune system targeting, and delivery system technology are paving the way for more effective vaccines. However, overcoming challenges such as cross-reactivity and safety concerns will require continued innovation and collaboration.